DIGLOSIA BAHASA SANGIHE (DIGLOSSIA OF SANGIHE LANGUAGE) - Jeane Mangangue (Balai Bahasa Sulawesi Utara, 2016)
Diglossia is a situation in which a language having functional division of varieties of language or languages in a community. The language used by Sangihe people is defined through the features of diglosia, that is particular and general language varieties. The aim of this research is to identify the styles of Sasahara and Sasalili languages, recognize when Sasahara and Sasalili used, and analyze the function of Sasahara and Sasalili languages. The theory used is Fishman’s theory. He defines diglossia as the language situation relatively stable in addition to the main dialect of language that includes regional standard, where there are very different things. This research uses qualitative method with sociolinguistics approach.The result shows that Sasahara and Sasalili languages are not only used by fishermen at the sea and farmers in the fields, but also used in the village for celebration, wedding party and in the lyrics of folk songs. Sasahara and Sasalili languages function as disguise language which used by people of Sangihe to avoid disaster that can disrupt their daily activity.